Thermoregulatory function during the Marathon - Kenefick, R. W.; Cheuvront, S. N.; Sawka, M. N. (Sports Medicine, 2007)
Marathon races are performed over a broad range of environmental conditions. Hyperthermia is a primary challenge for runners in temperate and warm weather, but hypothermia can be a concern during cool-wet or cold conditions. Body temperature during the marathon is a balance between metabolic heat production and exchange with the environment described by the heat balance equation. During exercise, core temperature is proportional to the metabolic rate and largely independent of a wide range of environmental conditions. In temperate or cool conditions, a large skin-to-ambient temperature gradient facilitates radiant and convective heat loss, and reduces skin blood flow requirements, which may explain the tolerance for high core temperature observed during marathons in cool conditions. However, in warmer environments, skin temperatures and sweating rates increase. In addition, greater skin blood flow is required for heat loss, magnifying thermoregulatory and circulatory strain. The combined challenge of exercise and environment associated with marathon running can substantially challenge the human thermoregulatory system.